Psikoedukasi Kesehatan Mental Pada Siswa SMA Negeri 2 Makassar - M. Ahkam Alwi; Kartika Cahyaningrum; Nurfajriyanti Rasyid; Rossy Allayda Syaiputri; Dibyo Restu Nugraha; Siti Zalsa Zeftira; Andi Nurfatimah Azzahra (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2024)
The aim of this research is to explore the impact of mental health psychoeducation on students at SMA Negeri 2 Makassar. This research uses a quantitative approach with a pre-test and post-test design. The research sample consisted of 120 students selected randomly. The psychoeducational intervention was carried out over six sessions, each lasting 90 minutes. Psychoeducational materials include an introduction to mental health, coping strategies, stress management, and interpersonal communication skills. The results showed that there was a significant increase in students' understanding of mental health after psychoeducational intervention (p < 0.05). In addition, there was a significant reduction in students' stress and anxiety levels (p < 0.05). Students also report improved communication skills and ability to deal with everyday problems. The conclusion of this research is that mental health psychoeducation is effective in increasing mental health knowledge and skills and reducing stress and anxiety among students at SMA Negeri 2 Makassar. The recommendation of this research is that mental health psychoeducation programs be implemented sustainably and expanded to other schools to support students' overall mental health.